The Intercultural Aspect of Teaching Arabic as a Foreign Language in Indonesia: - Kiki Kustina; M. Jafar Shodiq; Muhammad Syaifullah; Irhas Surohman (Mantiqu Tayr: Journal of Arabic Language, 2024)
The intercultural aspect is an important component in Arabic language teaching in Indonesia. That is because intercultural understanding is the basis for learners to be able to communicate and interact in Arabic effectively and efficiently. This paper examines the importance of the role of intercultural knowledge and understanding in teaching Arabic as a foreign language for Indonesian learners. The aim of this paper is to form an intercultural understanding of the teaching of Arabic language as an intercultural understanding for Indonesian students. The method used in studying this research is the method of studying literature with a qualitative approach. Data collection is done by managing material from books, journals, research results, and newspapers. The method used in reviewing this research is a literature study. To find out the use of cultural aspects in teaching Arabic, as a foreign language, this study will discuss four al, namely: (1) The Role of Culture in Language (2) Intercultural Competence in Language Learning (3) Language Teacher, Cultural Teacher (4) Intercultural in Arabic Language Culture. The conclusion of this paper is the importance of intercultural understanding in shaping intercultural aspects in the learning of Arabic at the level of Indonesian students. His contribution is that the paper can be used as a basic reference to shape the intercultural aspect and become a fundamental reference in developing the intercultural aspect of the Arabic language in Indonesia especially for students.